(3NUGFU aj PcQ GdfHj Udi Gddg Ydjg hSdes - (3GHf RcQj , CHh YHO Gddg eMeO Hf YHO GdQMef Hf RcQj,J (B1144 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPj LYd eOM GdeDef dQShdg GdCYXe hfTQg deMGSf LfGHg GdCaNe ef Cbhi GdCSHGH dJfejI eMHJg aj bdH GdeGOM hbdhH SGeYjg, efTC cGf GdeGOM Ce MGcjG hCdMb GdMGcj HGdefTF s
(3BNQgG (B:s
(3CYeGeg MeRI Ke CHhWGdH MLd VQGQ ebOe GdRHjQ YQGg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B197 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B140s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B284 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B- (3GdeZQH (B(115 (3O(B) s
Keywords: (3GdCOHs